Evaluasi Penggunaan Obat dan Kesesuaian Dosis Kemoterapi Body Surface Area (BSA) Pasien Kanker Payudara di RSUD Sekayu - Amelia, Kiki; Rusli, Doddy; Hikmah, Melinda (University Of Darussalam Gontor, 2022)
Research has been conducted on the description of the use of chemotherapy drugs and evaluation of the suitability of doses with the method of body surfeace area (BSA) in breast cancer patients (ca.mamae) at the Sekayu Regional General Hospital. The purpose of this study is to find out an overview of the use of drugs and doses given in chemotherapy patients. This research is descriptive with retrospective data retrieval method where data is obtained from the medical records of patients diagnosed with breast cancer in the period January-December 2019. Data retrieval technique in the form of total sampling, obtained 18 samples according to inclusion criteria.The results of the study obtained is on the use of chemotherapy drugs all patients get fac drug regimen as many as 18 patients (100%) and evaluation of dose conformity calculation obtained by 17 patients (94.44%) obtained an inappropriate dose and 1 patient (5,56%) get the appropriate dosage. From the results of the study obtained that the chemotherapy drug used is a first-line chemotherapy drug is in accordance with the treatment guidelines and the dose used has not been in accordance with the calculation based on the body surface area (BSA).